Pengaruh Rasio Likuiditas, Rasio Aktivitas, Rasio Leverage, dan Rasio Profitabilitas terhadap Earning Per Share - Dwiana Putri; Sri Suryoko; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2022)
This study aims to determine the effect of liquidity ratios, activity ratios, leverage ratios, and profitability ratios on Earning Per Share. The population in this study are pharmaceutical companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The type of data used is secondary data obtained from the publication of the Indonesia Stock Exchange. The number of samples in this study were 10 companies which were taken by purposive sampling method. The analytical technique used is multiple linear regression analysis using the SPSS version 24. The results of this study indicate that partially there are 3 variables that have a significant positive effect on Earning Per Share, namely the Current Ratio variable, Total Asset Turnover, and Debt to Asset Ratio, while Debt to Equity Ratio, Return on Assets, and Return on Equity variables have no significant effect on Earning Per Share. Simultaneously, the variables Current Ratio, Total Asset Turnover, Debt to Asset Ratio, Debt to Equity Ratio, Return on Assets, and Return on Equity have a significant effect on Earning Per Share. Penelitian ini bertujuan untuk mengetahui pengaruh rasio likuiditas, rasio aktivitas, rasio leverage, dan rasio profitabilitas terhadap Earning Per Share. Populasi dalam penelitian ini adalah perusahaan farmasi yang terdaftar di BEI periode 2016-2020. Jenis data yang dipakai merupakan data sekunder yang diperoleh dari publikasi Bursa Efek Indonesia. Jumlah sampel dalam penelitian ini sebanyak 10 perusahaan yang diambil dengan metode purposive sampling. Teknik analisis yang dipakai yaitu analisis regresi linear berganda menggunakan program SPSS versi 24. Hasil dari penelitian ini menunjukkan bahwa secara parsial terdapat 3 variabel yang berpengaruh signifikan positif terhadap Earning Per Share yaitu variabel Current Ratio, Total Asset Turnover, dan Debt to Asset Ratio, sedangkan variabel Debt to Equity Ratio, Return on Asset, dan Return on Equity tidak berpengaruh signifikan terhadap Earning Per Share. Secara simultan, variabel Current Ratio, Total Asset Turnover, Debt to Asset Ratio, Debt to Equity Ratio, Return on Asset, dan Return on Equity berpengaruh signifikan terhadap Earning Per Share.